Pengaruh Lingkungan Kerja Fisik dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan - Aprilia, Nabila Dinnar (Pascasarjana Universitas Primagraha, 2022)
In the current conditions, technology, politics, economy are very influential in facing competition, especially in the banking world. Generally, companies that can avoid competition will have low performance and product quality. This study aims to analyze and test the effect of the physical work environment and work motivation in increasing employee job satisfaction. The method used is quantitative with a causality approach. The population in this study are employees of PT. Bank Rakyat Indonesia (Persero) Tbk has as many as 107 respondents who also used the entire population as a sample. The data collection method is by questionnaire, which is directly distributed to respondents. The analytical tool used is the help of SPSS. The results of this study show that the hypothesis is rejected, namely that the physical work environment has no significant effect on job satisfaction. In contrast, work motivation significantly impacts job satisfaction. On the other hand, simultaneously, the variables of the physical work environment and work motivation significantly affect overall employee job satisfaction.